Past Conditional Subjectivities: Enacting Relationships with the Non-Human in the Work of Ana Mendieta - Tedford, Matthew Harrison (Text Matters: A Journal of Literature, Theory and Culture, 2022)
Inspired by what literary scholar Lisa Lowe calls “the past conditional temporality”—or the “what could have been”—this paper examines how the work of 20th-century Cuban American performance artist Ana Mendieta challenges modernist ontologies that separate the human from the non-human, simultaneously calling on older ways of being and demonstrating that they never disappeared. Many argue that the ecological crises of the Anthropocene are in large part due to the proliferation of modernist worldviews that set humans apart from the non-human world. The rise of European rationalist philosophies in the early modern period played a central role in the proliferation of instrumentalist relationships between humans and the non-human world. This paper explores how Mendieta’s Silueta and Rupestrian Sculptures series (from the 1970s and 1980s) resist the logic of European capitalism and colonialism, revealing that the relationships that rationalism sought to subdue have always existed, will continue to exist, and can proliferate. Symbolic communication is a key means of mediating and actualizing relationships between subjects, and so, if a non-instrumental relationship is possible between the human and non-human, visual art ought to be a possible means of enactment. Through Mendieta’s work, this paper considers the mechanisms by which this is possible. By considering meaning-making as a basis for life, the co-constitution of human/non-human subjectivities, and the inherent permeability of the category of the individual, this paper highlights counter-modernist visual art practices that are of special urgency in the age of the Anthropocene.